Find the best answers to your questions with the help of IDNLearn.com's expert contributors. Discover in-depth and trustworthy answers to all your questions from our experienced community members.
Sagot :
Sure, let's solve each equation step by step.
### Problem 6
Solve the equation: [tex]\( 25 - r^2 = 4r \)[/tex]
1. Rearrange the equation to set it equal to zero:
[tex]\[ 25 - r^2 - 4r = 0 \][/tex]
2. This is a quadratic equation in the form [tex]\( ar^2 + br + c = 0 \)[/tex]:
[tex]\[ -r^2 - 4r + 25 = 0 \][/tex]
3. Use the quadratic formula [tex]\( r = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = -1 \)[/tex], [tex]\( b = -4 \)[/tex], and [tex]\( c = 25 \)[/tex]:
[tex]\[ r = \frac{-(-4) \pm \sqrt{(-4)^2 - 4(-1)(25)}}{2(-1)} \][/tex]
[tex]\[ r = \frac{4 \pm \sqrt{16 + 100}}{-2} \][/tex]
[tex]\[ r = \frac{4 \pm \sqrt{116}}{-2} \][/tex]
[tex]\[ r = \frac{4 \pm 2\sqrt{29}}{-2} \][/tex]
4. Simplify:
[tex]\[ r = -2 \pm \sqrt{29} \][/tex]
So, the solutions are:
[tex]\[ r = -2 + \sqrt{29} \quad \text{and} \quad r = -2 - \sqrt{29} \][/tex]
### Problem 7
Solve the equation: [tex]\( 3x(x-2) = -7 \)[/tex]
1. Distribute and rearrange the equation to set it equal to zero:
[tex]\[ 3x^2 - 6x + 7 = 0 \][/tex]
2. This is a quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex]:
[tex]\[ 3x^2 - 6x + 7 = 0 \][/tex]
3. Use the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 3 \)[/tex], [tex]\( b = -6 \)[/tex], and [tex]\( c = 7 \)[/tex]:
[tex]\[ x = \frac{-(-6) \pm \sqrt{(-6)^2 - 4(3)(7)}}{2(3)} \][/tex]
[tex]\[ x = \frac{6 \pm \sqrt{36 - 84}}{6} \][/tex]
[tex]\[ x = \frac{6 \pm \sqrt{-48}}{6} \][/tex]
[tex]\[ x = \frac{6 \pm 2i\sqrt{12}}{6} \][/tex]
[tex]\[ x = 1 \pm \frac{2i\sqrt{3}}{3} \][/tex]
So, the solutions are:
[tex]\[ x = 1 - \frac{2i\sqrt{3}}{3} \quad \text{and} \quad x = 1 + \frac{2i\sqrt{3}}{3} \][/tex]
### Problem 8
Solve the equation: [tex]\( \frac{1}{2}(h-6) = 0 \)[/tex]
1. Multiply both sides by 2 to eliminate the fraction:
[tex]\[ h - 6 = 0 \][/tex]
2. Solve for [tex]\( h \)[/tex]:
[tex]\[ h = 6 \][/tex]
So, the solution is:
[tex]\[ h = 6 \][/tex]
### Problem 9
Solve the equation: [tex]\( (x+2)^2 = 0 \)[/tex]
1. Take the square root of both sides:
[tex]\[ x+2 = 0 \][/tex]
2. Solve for [tex]\( x \)[/tex]:
[tex]\[ x = -2 \][/tex]
So, the solution is:
[tex]\[ x = -2 \][/tex]
### Problem 10
Solve the equation: [tex]\( (w-8)(w+5) = 14 \)[/tex]
1. Expand the left side and rearrange the equation to set it equal to zero:
[tex]\[ w^2 - 8w + 5w - 40 = 14 \][/tex]
[tex]\[ w^2 - 3w - 40 = 14 \][/tex]
[tex]\[ w^2 - 3w - 54 = 0 \][/tex]
2. This is a quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex]:
[tex]\[ w^2 - 3w - 54 = 0 \][/tex]
3. Use the quadratic formula [tex]\( w = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = -3 \)[/tex], and [tex]\( c = -54 \)[/tex]:
[tex]\[ w = \frac{-(-3) \pm \sqrt{(-3)^2 - 4(1)(-54)}}{2(1)} \][/tex]
[tex]\[ w = \frac{3 \pm \sqrt{9 + 216}}{2} \][/tex]
[tex]\[ w = \frac{3 \pm \sqrt{225}}{2} \][/tex]
[tex]\[ w = \frac{3 \pm 15}{2} \][/tex]
4. Simplify:
[tex]\[ w = \frac{3 + 15}{2} = 9 \][/tex]
[tex]\[ w = \frac{3 - 15}{2} = -6 \][/tex]
So, the solutions are:
[tex]\[ w = 9 \quad \text{and} \quad w = -6 \][/tex]
### Problem 6
Solve the equation: [tex]\( 25 - r^2 = 4r \)[/tex]
1. Rearrange the equation to set it equal to zero:
[tex]\[ 25 - r^2 - 4r = 0 \][/tex]
2. This is a quadratic equation in the form [tex]\( ar^2 + br + c = 0 \)[/tex]:
[tex]\[ -r^2 - 4r + 25 = 0 \][/tex]
3. Use the quadratic formula [tex]\( r = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = -1 \)[/tex], [tex]\( b = -4 \)[/tex], and [tex]\( c = 25 \)[/tex]:
[tex]\[ r = \frac{-(-4) \pm \sqrt{(-4)^2 - 4(-1)(25)}}{2(-1)} \][/tex]
[tex]\[ r = \frac{4 \pm \sqrt{16 + 100}}{-2} \][/tex]
[tex]\[ r = \frac{4 \pm \sqrt{116}}{-2} \][/tex]
[tex]\[ r = \frac{4 \pm 2\sqrt{29}}{-2} \][/tex]
4. Simplify:
[tex]\[ r = -2 \pm \sqrt{29} \][/tex]
So, the solutions are:
[tex]\[ r = -2 + \sqrt{29} \quad \text{and} \quad r = -2 - \sqrt{29} \][/tex]
### Problem 7
Solve the equation: [tex]\( 3x(x-2) = -7 \)[/tex]
1. Distribute and rearrange the equation to set it equal to zero:
[tex]\[ 3x^2 - 6x + 7 = 0 \][/tex]
2. This is a quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex]:
[tex]\[ 3x^2 - 6x + 7 = 0 \][/tex]
3. Use the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 3 \)[/tex], [tex]\( b = -6 \)[/tex], and [tex]\( c = 7 \)[/tex]:
[tex]\[ x = \frac{-(-6) \pm \sqrt{(-6)^2 - 4(3)(7)}}{2(3)} \][/tex]
[tex]\[ x = \frac{6 \pm \sqrt{36 - 84}}{6} \][/tex]
[tex]\[ x = \frac{6 \pm \sqrt{-48}}{6} \][/tex]
[tex]\[ x = \frac{6 \pm 2i\sqrt{12}}{6} \][/tex]
[tex]\[ x = 1 \pm \frac{2i\sqrt{3}}{3} \][/tex]
So, the solutions are:
[tex]\[ x = 1 - \frac{2i\sqrt{3}}{3} \quad \text{and} \quad x = 1 + \frac{2i\sqrt{3}}{3} \][/tex]
### Problem 8
Solve the equation: [tex]\( \frac{1}{2}(h-6) = 0 \)[/tex]
1. Multiply both sides by 2 to eliminate the fraction:
[tex]\[ h - 6 = 0 \][/tex]
2. Solve for [tex]\( h \)[/tex]:
[tex]\[ h = 6 \][/tex]
So, the solution is:
[tex]\[ h = 6 \][/tex]
### Problem 9
Solve the equation: [tex]\( (x+2)^2 = 0 \)[/tex]
1. Take the square root of both sides:
[tex]\[ x+2 = 0 \][/tex]
2. Solve for [tex]\( x \)[/tex]:
[tex]\[ x = -2 \][/tex]
So, the solution is:
[tex]\[ x = -2 \][/tex]
### Problem 10
Solve the equation: [tex]\( (w-8)(w+5) = 14 \)[/tex]
1. Expand the left side and rearrange the equation to set it equal to zero:
[tex]\[ w^2 - 8w + 5w - 40 = 14 \][/tex]
[tex]\[ w^2 - 3w - 40 = 14 \][/tex]
[tex]\[ w^2 - 3w - 54 = 0 \][/tex]
2. This is a quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex]:
[tex]\[ w^2 - 3w - 54 = 0 \][/tex]
3. Use the quadratic formula [tex]\( w = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = -3 \)[/tex], and [tex]\( c = -54 \)[/tex]:
[tex]\[ w = \frac{-(-3) \pm \sqrt{(-3)^2 - 4(1)(-54)}}{2(1)} \][/tex]
[tex]\[ w = \frac{3 \pm \sqrt{9 + 216}}{2} \][/tex]
[tex]\[ w = \frac{3 \pm \sqrt{225}}{2} \][/tex]
[tex]\[ w = \frac{3 \pm 15}{2} \][/tex]
4. Simplify:
[tex]\[ w = \frac{3 + 15}{2} = 9 \][/tex]
[tex]\[ w = \frac{3 - 15}{2} = -6 \][/tex]
So, the solutions are:
[tex]\[ w = 9 \quad \text{and} \quad w = -6 \][/tex]
Thank you for using this platform to share and learn. Don't hesitate to keep asking and answering. We value every contribution you make. Your search for answers ends at IDNLearn.com. Thanks for visiting, and we look forward to helping you again soon.